Three new species of the genus Paraleucilla Dendy, 1892 (Porifera, Calcarea) from the coast of Bahia State, Northeastern Brazil - Cavalcanti, Fernanda F.; Menegola, Carla; Lanna, Emilio (Zootaxa, 2014)
Three new species of calcareous sponges from the coast of Bahia State, NE Brazil are described. All of them belong to the genus Paraleucilla (Calcaronea, Leucosolenida, Amphoriscidae): P. solangeae sp. nov., P. oca sp. nov., and P. incomposita sp. nov. The number of species recorded from the Bahia coast has thus increased from 10 to 13. Including these new species, there are now 50 calcareous sponge species known from the entire Brazilian coast. Paraleucilla is now composed of 11 species, six of them occurring along the southwestern Atlantic Ocean. The remaining species occur mainly in the Indian Ocean, and also in the Pacific Ocean, Red Sea and Mediterranean Sea. An identification key for all Paraleucilla species is provided. This paper is dedicated to the memory of Professor Solange Peixinho, to acknowledge her contribution to our understanding of the biodiversity of Calcarea from the Bahia coast in Brazil.